Communication Challenges in the Eve of the 4.0 Industrial Revolution - VOINA, Andreea Nicoleta; PAVELEA, Anișoara (Presa Universitară Clujeană, 2022)
Communication challenger in the eve of the 4.0 industrial revolution is a comprehensive volume including papers presented within the International Students’ Conference on Communication, organized by the Department if Communication, Public Relations and Advertising, Faculty of Political, Administrative and Communication Sciences, Babes-Bolyai University, Cluj-Napoca, Romania, between the 26th and the 27th of April 2018. The topics of the papers are related to nowadays communication science and reflect upon the interests of the current students in communication science majors.